Islamic Education Institutional Reform: An Analysis of Challenges and Opportunities in the Digitalization Era - Maftuhah Maftuhah; Khoeron Khoeron; Umi Rosidah; Richway Richway; Mira Rahmayanti; Tobroni Tobroni; Faridi Faridi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid advancement of digital technology has significantly transformed the education sector, including Islamic educational institutions. These institutions are urged to adapt through institutional reform to remain relevant in the digital era. This study employed a qualitative approach using literature review and participatory observation. Data were collected from relevant academic publications (2019–2024), institutional reports, and observations at selected Islamic educational institutions. The findings reveal that Islamic educational institutions face several challenges in the digitalization process, including the digital divide, resistance to change, limited infrastructure, and insufficient digital competencies among teachers. However, the digital era also presents substantial opportunities, such as broader access to learning resources, flexible learning environments, improved institutional management, and global collaboration. Institutional reform in Islamic education requires strategic efforts such as infrastructure development, human resource digital literacy enhancement, curriculum integration with digital competencies, and the use of digital platforms for da'wah and religious moderation. These efforts are essential to maximize the potential of digital transformation while maintaining Islamic values.